Faktor-Faktor Yang Berhubungan Dengan Kejadian Glaukoma Di Rumah Sakit Mata Lampung Eye Center Bandar Lampung - Amelia, Erry Rizki; Himayani, Rani; Suharmanto, Suharmanto (Medula, 2024)
Glaucoma is a chronic progressive optic neuropathy characterized by elevated intraocular pressure, cupping of the optic disc and visual impairment with visual field defects. Every year the number of glaucoma is increasing and become the second common cause of blindness. This study aims to determine what factors related to the incidence of glaucoma at the Eye Hospital Lampung Eye Center Bandar Lampung. This study used an analytic observational design with a cross sectional approach. The data used who were sourced from secondary data in the form of medical records that are recorded data were patient characteristics, main complaint, history of hypertension and incidence of glaucoma. This respondents consisted of 134 glaucoma patients who showed the results that most respondents are in the age group >60 years (43.3%), male (53%), had high education status (64,9%), had no history of hypertension (73.1%), the main complaint with visual impairment (59,7%) and the incidence of primary glaucoma type of glaucoma (47.8%) . There were no correlation among age (p = 0,468), gender (p = 0.148), education status (p = 0.116), a history of hypertension (p = 0.259) and main complaint (p = 0.087) with the incidence of glaucoma at Eye Hospital Lampung Eye Center Bandar Lampung. There were no correlation among the characteristic features, history of hypertension and main complaint of glaucoma with the incidence of glaucoma.